PKD1 participates in the processing of aortic dissection via regulating vascular smooth muscle cell contraction and MAPK signaling: PKD1’s role in aortic dissection pathway - Feng, Junbo; Hu, Yuntao; Peng, Peng; Li, Juntao; Ge, Shenglin (Cellular and Molecular Biology, 2023)
Aortic Dissection (AD) is a cardiovascular emergency with high mortality, of which one feature is the phenotypic switch of vascular smooth muscle cells (VSMCs). Transient Receptor Potential Channel Interacting (PKD1) has been regarded as one regulator as well as one biomarker for AD. However, multiple candidate pathways were reported though which PKD1 regulates AD in previous study, a comprehensive insight is still absent. In this study, we compared the AD and normal samples in transcriptome scale, and detected 717 PKD1-related differential expressed genes, which enriched in mitogen-activated protein kinase (MAPK) signal transduction (AD tissue preference) and VSMC contraction pathway (normal tissue preference). Furthermore, we also found two important functional hub genes in PKD1 regulation, JUN and ACTN2, and established a carnal-miRNA-mRNA network. Our study demonstrated the co-regulation of muscle development and signal transduction in AD’s progression, and also provided the genetic basis for the following mechanism research with AD.